From Trust to Loyalty: The Mediating Role of Customer Satisfaction in ShopeePay Reuse Intention - Pardede, Jeremy Anggi; Hendrawan, Dimas (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Reuse intention is a person's intention to reuse a product or service. In the context of technology, there are various factors that influence users to reuse a product or service. This study aims to determine and analyze the effect of the trust variable on the reuse intention variable with customer satisfaction as an intervening variable on ShopeePay e-wallet service users in Malang City. This type of research is explanatory research which aims to test hypotheses related to various variables to find cause and effect. This study used a sample of 163 respondents obtained through distributing questionnaires online. The data analysis technique used is Partial Least Square with the Smart PLS version 4.0 program. The results of this study indicate that the trust variable has a significant influence on reuse intention. Trust variables also have a significant influence on customer satisfaction. The customer satisfaction variable has a significant influence on reuse intention. Furthermore, the customer satisfaction variable has a significant influence as an intervening variable between the trust variable and the reuse intention variable on ShopeePay users in Malang City.